2016
DOI: 10.1007/s10457-016-0048-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agroforestry parklands on crop yield and income generation: case study of rainfed farming in the semi-arid zone of Sudan

Abstract: National food security has been a major policy goal in Sudan since the country gained its independence in 1956. One of the fundamental reasons is to ensure the social welfare for people living in rural areas. In this study we aimed to analyse how farmers secure their food and generate income in the semi-arid Sennar State in Sudan, using two selected sites, El Dali and El Mazmum, as examples. We interviewed 281randomly sampled household heads, of which 145 at El Dali and 136 at El Mazmum, between July and Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…Thus, bamboo-based agroforestry could be used to enhance productivity and economic returns in semi-arid areas of India. Increased average yields for sesame, pear millet, and sorghum were observed in parkland agroforestry areas over a ten-year period in the semi-arid areas of Sudan, and land tenure reforms were needed to influence farmers to retain more trees in parklands [85].…”
Section: The Use Of Agroforestry To Enhance Soil Productivity and Its...mentioning
confidence: 99%
“…Thus, bamboo-based agroforestry could be used to enhance productivity and economic returns in semi-arid areas of India. Increased average yields for sesame, pear millet, and sorghum were observed in parkland agroforestry areas over a ten-year period in the semi-arid areas of Sudan, and land tenure reforms were needed to influence farmers to retain more trees in parklands [85].…”
Section: The Use Of Agroforestry To Enhance Soil Productivity and Its...mentioning
confidence: 99%
“…Among the different existing options, agroforestry is one of the environmentally friendly approaches that help farmland soil improve and checked for smallholder farmers [9,11]. It has many provisional, regulating, and cultural services, considered as climate-resilient and adaptation mechanisms [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It has many provisional, regulating, and cultural services, considered as climate-resilient and adaptation mechanisms [12][13][14][15]. Maintenance and improving existing practices and incorporation of multipurpose trees (MPTs) on farms are recognized as critical interventions to increase agricultural productivity in a sustainable way [9,11]. Trees are advantageous for protecting environmental degradation, reducing external input costs, generally considered as a means for organic farming which assures agricultural sustainability [16].…”
Section: Introductionmentioning
confidence: 99%
“…Rahman et al confirmed that agroforestry practices presented clear differences in net economic income between different tree species or crops [18]. Peanut, millet and sorghum are cultivated in more than 50% of agroforestry systems in Sudan, but the greatest benefit over a 10-year period is achieved in the tree/sorghum, /pearl millet, and /sesame agroforestry systems [45]. Ngwira et al reported that a main crop intercropped with other crops produced completely different income levels through contrast tests [46].…”
Section: Economic Advantagementioning
confidence: 99%